The human in command exploring the modern military experience - McCann, Carol; Pigeau, Ross (Kluwer Academic/Plenum Publishers, 2000)
Whether involved in disaster relief, peacekeeping operations, or war, militaries from all nations deal in the common currency of human conflict. And although technology has come a long way in assisting the resolution of some of these conflicts, inevitably human conflict requires human intervention. The purpose of this book is to explore and understand the implications of this human intervention and the ways that science can make it more effective. The book brings together experienced military leaders and researchers in the human sciences to offer current operational experience and scientific thought on the issue of military command, with the intention of raising awareness of the uniquely human aspects of military command. It includes chapters on the personal experiences of senior commanders, new concepts and treatises on command theory, and empirical findings from experimental studies in the field.